THE EFFECT OF TAX AVOIDANCE, PROFITABILITY, AND LEVERAGE ON DIVIDEND POLICY: LIQUIDITY AS MODERATING VARIABLE - Fitria Hanifah; Ekaningtyas Widiastuti; Najmudin Najmudin (Transpublika Publisher, 2024)
This study examines the effect of tax avoidance, profitability, and leverage in dividend policy; this case study was conducted at IDX80. IDX80 is a list created by the Indonesian stock exchange where this index measures the price performance of 80 stocks with high liquidity and large market capitalization. This research was conducted in 2018 - 2021, using a purposive sample method; 96 samples were obtained. The results of this study indicate that tax avoidance does not affect the company's dividend policy, while profitability and leverage affect dividend policy. Legal tax avoidance by the company does not have a direct effect on the company's dividend policy. So, even though the company practices tax avoidance, this will not have a significant effect on the decision to distribute dividends. Profitability has a positive and significant impact on dividend policy, which means that if the company's profitability increases, the dividend policy will also increase. Then leverage has a negative and significant effect on dividend policy, which means that when the company's leverage is high, the dividends distributed by the company will decrease. Then, this study uses liquidity as a moderating variable, showing that liquidity moderates the relationship between profitability and dividend policy. In contrast, high liquidity can weaken the relationship between profitability and dividend policy.